Media Concentration and right to information in Peru - Mejía Alarcón, Roberto Marcos (2018)
The advancement of information and communication technologies is driven to unprecedented dimensions. We can communicate in real time almost from any point of the planet. However, the companies that make it possible are few. Are we facing a mega concentration of global-level media? The right to information, seen as a human and fundamental right, in theory equal for all, but in reality, fully accessible only to those who have free and permanent access to the mass media, or have the influence or power to do what. The social communication media, like those vehicles or channels that make it possible to exercise in a better way, our human right to have an opinion, express our thoughts, communicate  what we want to our fellowmen and receive the information that is of our interest, are holders of a public service, very necessary and linked to the full enjoyment and exercise of fundamental rights. The relationship of both in the current moments, is the subject of this article.